Síndrome de Down por translocación robertsoniana: cuando el cariotipo de los padres marca la diferencia - Franco Bustamante, Kelly Cinthia (2026)
Down syndrome (DS) is the most common chromosomal abnormality in humans, characterized by a variable phenotype that includes typical facial features, psychomotor developmental delay, intellectual disability, and congenital malformations, particularly cardiac defects. Although most cases result from free trisomy 21, between 2 % and 4 % are caused by Robertsonian translocations, which have significant implications for reproductive risk. We report the case of a male infant referred for congenital heart disease and psychomotor developmental delay. Physical examination revealed the classic DS phenotype, and echocardiography confirmed a ventricular septal defect. Cytogenetic analysis using GTG banding revealed a karyotype of 46,XY,rob(21;21)(q10;q10),+21, confirming the presence of a Robertsonian 21/21 translocation. Parental karyotypes were normal. The recurrence risk of Robertsonian translocation DS varies according to its origin: if inherited from a 21/21 carrier, it is close to 100 %, whereas in de novo translocations, it is approximately 2 %.  Therefore, karyotyping of both parents is essential, as determinng the origin of the translocation enables appropriate genetic counseling. This process involves estimating the recurrence risk, guiding reproductive decision-making, and recommending strategies such as preimplantation genetic diagnosis and noninvasive prenatal screening for future pregnancies. In summary, this report highlights the importance of a multidisciplinary approach and cytogenetic analysis to optimize patient care and prevent recurrence in families affected by DS associated with Robertsonian translocations.